Pengembangan Multimedia Interaktif dengan Menggunakan Adobe Animate CC pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas VI Semester I di SD Negeri 10 OKU: Interactive Multimedia Development Using Adobe Animate CC in Natural Science Subjects for Grade VI Semester I at SD Negeri 10 OKU - Isa, Yamanto; Eriyanti, Eriyanti; Rahmi, Juhaidatur; Novita, Ria (ITScience (Information Technology and Science), 2024)
The purpose of this study was to develop Interactive Multimedia Using Adobe Animate CC in Natural Science Subjects for Grade VI Semester I at SD Negeri 10 OKU. This type of research is a development research (Research and Development) with a procedural development model. In this study, the trial subjects went through four stages, namely the expert evaluation stage, the individual evaluation stage, the small group evaluation stage, and the field trial stage. Data collection techniques were through questionnaires. The data analysis technique used was the percentage formula. The results of the expert evaluation, namely media experts, obtained a value of 80.72% with a Good predicate, design experts with a value of 88.92% with a Very Good predicate, material experts with a value of 87.18% with a Very Good predicate. The next stage was an individual evaluation, obtained a value of 90.72% with a Very Good predicate. After that, a small group evaluation was carried out, obtained a value of 91.16% with a Very Good predicate. Furthermore, a field trial was carried out. The results of the product trial data acquisition showed the level of product feasibility in the Very Good criteria, with a total value of 87.69%. Thus, it can be concluded that the product has a level of feasibility with very good criteria to be used as a medium in Natural Science learning activities in semester I of Grade VI of Elementary School.